HRPS - “Welfare Emergency Technical Aid” Final Individual Assignment - Mammadov, Shukur (ADA University, 2019)
Azerbaijan is an among of developing countries. This is not secret that Azerbaijan economy is oil driven economy and with latest worldwide conjecture their high demand to the oil and with oil price increase country economy also positively affecting. Government seriously intended to develop nonoil sector. “As a result of the measures taken in Azerbaijan, it is projected that the nonoil sector will grow 3.9 percent. Considering the changes taking place in the global economy and the economic situation in our main partner countries, Azerbaijan’s Economy Ministry has prepared socio-economic indicators for 2019 and for the medium term over the next three years,” (https://www.azernews.az/business/140839.html) certainly with non-oil sector development country population income level is increasing and welfare status also positively changing. Azerbaijan made high percentage point (pp) in construction and trade & repair services areas on nonoil economy. (https://www.economy.gov.az/en/article/non-oil-industry/22771). There 1.2 pp for construction and 1.5 pp increase in repair and vehicle services. This is obvious fact for construction business domination in nonoil economy sector. Following to construction other business areas in this domain also developing logically like, proprietary and welfare repair services too. Surely in big cities and other urbanized areas of the country lifestyle is changing. With digitalization trends and construction materials development and demand for qualities require different approach to welfare complexities management. Where in this business plan paper professional company establishment for welfare complexities management proposed with their opportunity study, financial projection and marketing promotion development. There great opportunity in the market for professional welfare complexity management company. Such as, while looking to European countries, there already established firms which dealing with all kind of welfare complexities. There also tendencies in CIS countries for professional welfare problems management services. Much details already studied in industry analyze chapter of this paper. Three years financial analyze done for proposed business. Approximately 104.5K AZN will be required, which 50K own investment and 60K loans considering to be attracted for company launch. Additional 182.6K AZN investment also will be needed upon planned sales growth. Within first year 12th month company will become to its breakeven point. According to sales forecast company will have approximately 1-2 % monthly growth expected in sales volume. Company net profits approximated 134.6K, 100.9K, 166.9K during three years accordingly. For marketing part of the business, clear marketing strategy and famous 4P’s model were developed. Digital marketing will be widely used for successful marketing activities. As a result, strong brand, strategic partnership and target audience awareness will be created. The result show that there demand in the market for welfare complexity management services and proposed business address the needs of market. Studied financial analyze show that, business is feasible and can provide sustainable growth and profit. Moreover, business has great future potential to enter into construction and proprietary business. As country nonoil economy area, the construction promises bright growth future. Considering this fact proposed business also carry less risk as always company either can be sold or company assets are always might be open to sale as exit strategy. Considering above sayings, I highly recommend to potential investors to invest to this business and become a partner in such a virgin market.
Keywords: Business; Economic security.; Economic security -- Azerbaijan.; Public welfare.; Public welfare -- Azerbaijan.; Human services.; Human services -- Azerbaijan.